Pengaruh Citra Merek, Variasi Produk, dan Harga Bundling Terhadap Keputusan Pembelian Pada Konsumen X - Muhammad Izul Haq; Taufik Akbar; Karari Budi Prasasti (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the influence of brand image, product variety, and bundling price on purchasing decisions among X consumers. The method used is a quantitative approach with a causal research design, so as to be able to explain the cause-and-effect relationship between variables. The research data was obtained by distributing questionnaires to 96 respondents who are active consumers of X. To ensure data quality, a series of tests were conducted including validity, reliability, normality, linearity, multicollinearity, and heteroscedasticity. The main analysis used multiple linear regression supported by t-tests, F-tests, and coefficient of determination (R²) processed using SPSS software version 26. The results showed that brand image had a significant effect on purchasing decisions, indicating that consumers' positive perceptions of X's reputation were able to encourage higher purchasing interest. Bundling price also proved to have a significant effect, because the strategy of combining package prices was considered to provide economic benefits and added value for consumers. In contrast, product variety did not have a significant effect, indicating that consumers place more emphasis on brand image and pricing strategies than simply menu diversity. However, when tested simultaneously, all three variables were still shown to have a significant influence on purchasing decisions. The coefficient of determination value of 0.594 indicates that the combination of the three variables can explain 59.4% of the variation in purchasing decisions, while the remaining 40.6% is influenced by other external factors such as service quality, consumer trends, promotions, and customer experience. These findings reinforce the understanding that a strong brand image-based marketing strategy and the implementation of appropriate bundling prices can be key to increasing consumer appeal. For local coffee businesses like X, this study provides practical implications to focus more efforts on strengthening brand image, creating a consistent consumer experience, and optimizing pricing strategies.